Post-traumatic stress disorder in German youth: representative claims data pre- vs. intra-COVID-19-pandemic - Jule Leickert; Stephan Zillmer; Christian J. Bachmann; Annika Vivirito; Dirk Enders; Christoph U. Correll; Charlotte Jaite (European Journal of Psychotraumatology)
Background: COVID-19-exposure and related restrictions may have contributed to the development or exacerbation of post-traumatic stress disorders (PTSD), especially in youth. However, data in this population is lacking.Objective: This study aimed to provide a thorough insight into the epidemiology and psychiatric comorbidities of PTSD as well as in- and outpatient treatment utilisation by those affected during vs. before COVID-19 in a representative sample of children and adolescents statutorily insured in Germany.Methods: The study is based on anonymized claims data of statutory insured youth aged 0.0–17.9 years from the InGef research database, which is representative of the German population. Prevalence, incidence, comorbidities of PTSD (ICD-10: F43.1, F43.8, F43.9) and in- and outpatient treatment for those affected were compared pre-COVID (01/2018–03/2020; N = 710.629) vs. intra-COVID (04/2020–12/2021; N = 698.108) using descriptive statistics, χ2 tests, Welch-tests and interrupted time series analyses stratified by sex, age (children: 0–13 years; adolescents: 14–17 years), and socio-economic status (SES).Results: PTSD prevalence decreased intra-COVID (girls: 0.8%, n = 2.595 vs. 0.6%, n = 1.965; OR = 0.77 [0.73, 0.82]; boys: 0.6%, n = 2.066 vs. 0.4%, n = 1.547; OR = 0.76 [0.71, 0.81]). Quarterly incidence in female children with high SES showed a significant increase in slope pre-COVID to intra-COVID (p = .018). Externalising comorbidities increased especially in female adolescents (OR = 1.34 [1.05, 1.72]). Psychotherapy utilisation decreased in male children with low SES (OR = 0.63 [0.41, 0.98]) and increased in adolescent girls with low SES (OR = 1.73 [1.09, 2.74]). Hospitalisations among female adolescents only decreased for those with low SES (OR = 0.67 [0.38, 1.19]).Conclusions: We observed similar decreases in clinical PTSD-diagnoses for girls and boys, possibly reflecting overstretched health services, particularly at an early stage of COVID-19. However, treatment utilisation shows sex and SES differences that cannot be fully explained by our data.